Protective effect of lycopene on diethylnitrosamine-induced oxidative stress and catalase expression in rats - Kaya, Emre; Yilmaz, Seval; Ceribasi, Ali Osman; Telo, Selda (Ankara Univ Press, 2019)
The purpose of this study is to investigate the protective role of lycopene on diethylnitrosamine (DEN)-induced hepatotoxicity using biochemical and histopathological approaches. The rats were divided into 5 groups as control, lycopene, DEN, lycopene+DEN and DEN+lycopene. DEN was administered to rats at 200 mg/kg, a single dose intraperitoneally for 30 days. Lycopene was administered to rats every other day at 10 mg/kg, gavage for 10 days. Lycopene administration was started 10 days before the DEN administration in lycopene+DEN group and together with the DEN administration in DEN+lycopene group. In this study, malondialdehyde (MDA), reduced glutathione (GSH) levels, catalase (CAT), glutathione peroxidase (GSH-Px), glutathione-S-transferase (GST), superoxide dismutase (SOD) activities and the expression levels of the CAT enzyme were measured in blood and liver tissues. DEN caused the oxidative stress by the increased MDA level and the reduced GSH level, antioxidant enzyme activities in tissues. Lycopene administration produced amelioration in biochemical indices of hepatotoxicity in both blood and liver tissues when compared to DEN group; simultaneous-administration with DEN has been more effective. It was determined to increase expression levels of the CAT enzyme in the DEN group in RT-PCR. The improvement in expression levels in DEN+lycopene group was observed to be better than the lycopene+DEN group. Histopathologically, many different histopathological changes were observed in liver tissues of DEN and lycopene+DEN groups, it was determined that these changes reduced in DEN+lycopene group. The results from the present study indicate that lycopene exhibits good hepatoprotective and antioxidant potential against DEN-induced hepatocellular damage in rats.
Ratlarda likopenin dietilnitrozamin kaynaklı oksidatif stres ve katalaz ekspresyonu üzerine koruyucu etkisi
Keywords: Antioxidant; CAT expression; diethylnitrosamine; lycopene; oxidative stress